Nanomaterials in wound infeetion care for senile diabetes: current research and developments - Yiran Liu; Xue Bai; Hui Ren; Baofeng Guo (Guoji laonian yixue zazhi)
Wound infections in elderly diabetic patients represent a severe complication of diabetes, with diabetic foot ulcers being the most common manifestation.Due to impaired immune function and the prolonged course of the disease, elderly patients often struggle to control wound infections, leading to increased medical costs, extended hospital stays, higher rates of amputation and mortality.As bacterial resistance becomes more prevalent, traditional oral or intravenous antibiotics are increasingly ineffective in treating wound infections in elderly diabetic patients.In contrast, emerging nanomaterials offer promising prospects in antibacterial therapy, owing to their superior biocompatibility, targeted action, controlled release, and low toxicity.This article reviews the latest research on the antibacterial mechanisms of nanomaterials and explores their potential as a novel strategy for treating wound infections in elderly diabetic patients.